A1AT polymorphisms may be associated with clinical characteristics of retrovirus infections in a mixed ethnic population from the Brazilian Amazon region - Thalita Camêlo da Silva Ferreira; Maria Alice Freitas Queiroz; Gustavo Adolfo Argañaraz; Ricardo Ishak; Antonio Carlos Rosário Vallinoto; Enrique Roberto Argañaraz (International Journal of Infectious Diseases, 2017)
Objectives: This study investigated the association of alpha-1-antrypsin deficiency (A1AT; S and Z polymorphisms) with HIV-1 and HTLV-1 infection. Methods: Blood samples from 201 HIV-1-infected and 115 HTLV-1-infected individuals were examined and compared with those from 300 healthy controls. Genotyping of A1AT (S and Z) and quantification of plasma viral load were performed using RT-PCR, and the CD4+/CD8+ T-cell count was determined by flow cytometry. Results: The wild-type MM genotype showed the highest frequency in each of the three groups investigated. SS and ZZ homozygous genotypes (variants) were observed only among HTLV-1 patients and controls, respectively. Genotype MS was significantly less frequent in HTLV-1-positive persons than in controls. Statistically significant differences were observed when comparing genotype frequencies between symptomatic and asymptomatic HTLV-1-infected persons. The distribution of plasma HIV-1 viral load among individuals with different genotypes of A1AT polymorphism also differed significantly. Conclusions: The results suggest that A1AT polymorphisms may be associated with human retrovirus infections when dealing with an ethnically mixed population from the Amazon region of Brazil. Keywords: A1T1, Polymorphisms, HIV-1, HTLV-1